A Ka-band low-loss self-biased composite ferrite material and preparation method

By synthesizing NiZn and BaM ferrite materials in one pot, and introducing dopants to regulate the magnetic moment exchange coupling, the problem of existing materials being difficult to combine multiple excellent properties has been solved, and the project of Ka-band micro-integrated circulator has been realized. application.

CN118955112BActive Publication Date: 2025-01-24UNIV OF ELECTRONICS SCI & TECH OF CHINA
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411456112.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-18
Publication Date
2025-01-24
Estimated Expiration
2044-10-18

AI Technical Summary

Technical Problem

The existing Ka-band low-loss self-biased microwave ferrite materials are difficult to have high 4πMs, Mr/Ms, Ha, Hc and low ΔH and tanδε characteristics, which limits the engineering application of Ka-band micro-integrated circulators.

Method used

Through formula and process design, solid-phase sintering method is used to synthesize NiZn and BaM ferrite pre-sintered materials in one pot, control the reaction generation of spinel-type intermediate products and ferrite, enhance the magnetic moment exchange coupling effect, and introduce doping Impurities such as CuO and SiO2 repair lattice defects and improve sintering densification.

Benefits of technology

The Ka-band low-loss self-biased composite ferrite material is realized with high 4πMs, Mr/Ms, Ha, Hc and low ΔH, tanδε characteristics, and is suitable for the design and application of Ka-band micro-integrated circulators.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

A Ka-band low-loss self-biased composite ferrite material and a preparation method thereof, belonging to the technical field of ferrite material preparation. The composite ferrite material comprises NiZn and BaM ferrite materials; the NiZn ferrite material comprises 40-60 mol% NiO, 1-5 mol% CuO, 1-5 mol% ZnO, 40-50 mol% Fe 2 O 3 ; BaM ferrite materials include 10~20 mol% BaO, 1~10 mol% ZnO, 1~5 mol% La 2 O 3 , 1~10 mol%CuO, 60~75 mol%Fe 2 O 3 The Ka-band low-loss self-biased composite ferrite material prepared by the present invention has both high 4π M s , M r / M s , H a , H c and low Δ H tan d ε Characteristics, suitable for the design and application of Ka-band micro-integrated circulator.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of ferrite material preparation, and in particular relates to a Ka-band low-loss self-biased composite ferrite material and a preparation method thereof. Background Art

[0002] High frequency and integration are the main development directions of microwave communication systems in the future. The Ka band has the advantages of large bandwidth and high resolution. Its bandwidth is twice that of the Ku band and five times that of the C band. Ka-band satellite communication is particularly suitable for broadband digital transmission, high-speed satellite communication and other needs. It can provide conditions for gigabit broadband digital transmission, high-definition television (HDTV), satellite news gathering (SNG), VSAT services, direct-to-home (DTH) services and personal satellite communications. Transceiver components are the core components of microwave communication systems. They play a vital role in information sharing and inter-stage isolation, and become the key factors in determining the reliability and stability of the entire system. With the continuous development of microsystem technology, transceiver components have gradually realized 2.5D technology. Embedded chips and via interconnections have realized the integration of modules such as amplifiers, limiters, and attenuators in transceiver components. However, it is still necessary to reserve space for the external magnetic steel of the microstrip circulator. For example, the existing Ka-band circulator needs to add an external magnetic steel with a height of 3.5 mm to the ferrite substrate to provide a bias magnetic field to realize the circulation function. The technology that restricts the integration of transceiver components is the low-loss self-biased microwave ferrite material used in them. This type of material serves as the "heart" of microwave devices, completing the transmission and coupling of electromagnetic wave signals and is the basic supporting material for microstrip circulators.

[0003] In the study of low-loss self-biased microwave ferrite materials, V. Laur et al. prepared saturation magnetization intensity 4π by solid phase sintering method. M s 4200 Gs, remanence ratio M r / M s is 0.90, anisotropic field H a is 21 kOe, and the ferromagnetic resonance line width Δ H For 1.5 kOe hexagonal microwave ferrite material, Δ H Large, and the coercivity of the material is not reported H c and dielectric loss tan d ε L. Peng et al. used microwave sintering method combined with low temperature sintering technology to prepare hexagonal microwave ferrite materials. When the La-Ni substitution amount was 0.2, the material showed high H a and H c, whose values ​​are 1.81 T and 4.1 kOe, respectively. The 4π M s , M r / M s , Δ H and tan d ε V. Sharma et al. used the sol-gel method to prepare composite microwave ferrite materials. As the YIG content increased, H a Gradually decrease, Δ H From 2000Oe to 385Oe, but H c <600 Oe, 4π not reported M s , M r / M s and tan d ε C. Pahwa et al. used a one-step sol-gel method to prepare composite microwave ferrite materials. x = 0.3, the 4π M s reaches the maximum, but H c However, it dropped from the initial 3600 Oe to 690 Oe. H c Severe deterioration, e Reached a maximum of 28, not reported M r / M s , Δ H and tan d ε Although the above materials have excellent performance in some parameters, they cannot achieve high 4π M s , M r / M s , H a , H c and low Δ H tan d ε Due to its characteristics, the developed Ka-band micro-integrated circulator cannot meet the requirements of engineering applications.

[0004] Based on the above, the present invention proposes a Ka-band low-loss self-biased composite ferrite material and a preparation method, and realizes the composite of two microwave ferrite materials, NiZn and BaM, through formulation and process design, and develops a composite ferrite with high 4π M s , M r / M s , H a , H c and low Δ H tan d ε Characteristics of microwave ferrite materials. Summary of the invention

[0005] The purpose of the present invention is to propose a Ka-band low-loss self-biased composite ferrite material and a preparation method, in view of the fact that the low-loss self-biased composite ferrite material involved in the current technology is difficult to meet the engineering application requirements of Ka-band micro-integrated circulators. The material has high 4π M s , M r / M s , H a , H c and low Δ H tan d ε Features, fundamentally solve the existing Ka-band microstrip circulator micro-integration problem.

[0006] The core idea of ​​the present invention is: according to the dynamic process of grain growth of two microwave ferrites NiZn and BaM, NiZn and BaM ferrite pre-sintered materials are synthesized in one pot based on the solid phase sintering method. BaM ferrite is generated by the reaction of spinel intermediate products and Fe2O3. In the formula system, the iron-deficient formula is used to reduce the electrons in Fe 2+ ~Fe 3+ Migration between d ε , the introduction of Zn 2+ and Cu 2+ Regulating the ion occupancy distribution of two microwave ferrites, NiZn and BaM, to improve 4π M s and M r / M sDuring the pre-sintering process, a multi-step pre-sintering technology is used to regulate the reaction of spinel intermediate products, NiZn and BaM ferrite, enhance the exchange coupling between the magnetic moments of NiZn and BaM ferrite, and convert the high M r / M s , H a , H c Features grafted on high 4π M s , low Δ H tan d ε The introduction of low melting point CuO in the composite additive can repair the lattice defects of NiZn and BaM ferrites, improve sintering densification, and further increase 4π M s and M r / M s , reduce Δ H and tan d ε ; Introduce high melting point SiO2 to narrow the particle size distribution and improve H a and H c .

[0007] The key technical problem solved by the present invention is that the low-loss self-biased composite ferrite material in the Ka band cannot have both high 4π M s , M r / M s , H a , H c and low Δ H tan d ε The Ka-band low-loss self-biased composite ferrite material and its preparation method are provided to solve the technical problems of the characteristics. The Ka-band low-loss self-biased composite ferrite material developed has both high 4π M s , M r / M s , H a , H c and low Δ H tan d ε Characteristics. The technical solutions adopted by the present invention are as follows:

[0008] A Ka-band low-loss self-biased composite ferrite material, characterized in that it comprises a main phase and a dopant;

[0009] The main phase includes NiZn ferrite material and BaM ferrite material, wherein the NiZn ferrite material includes 40-60 mol% NiO, 1-5 mol% CuO, 1-5 mol% ZnO, and 40-50 mol% Fe2O3, and the BaM ferrite material includes 10-20 mol% BaO, 1-10 mol% ZnO, 1-5 mol% La2O3, 1-10 mol% CuO, and 60-75 mol% Fe2O3; the mass ratio of the NiZn ferrite material to the BaM ferrite material is 1:1-1:4;

[0010] The weight percentage of the dopant in the main phase, calculated as oxide: 0.1~0.5 wt.% CuO and 0.1~0.5 wt.% SiO2.

[0011] A method for preparing a Ka-band low-loss self-biased composite ferrite material comprises the following steps:

[0012] Step 1: Ingredients

[0013] Weigh the NiZn ferrite raw material according to the ratio of "40-60 mol% NiO, 1-5 mol% CuO, 1-5 mol% ZnO, 40-50 mol% Fe2O3"; weigh the BaM ferrite raw material according to the ratio of "10-20 mol% BaO, 1-10 mol% ZnO, 1-5 mol% La2O3, 1-10 mol% CuO, 60-75 mol% Fe2O3"; mix the NiZn and BaM ferrite raw materials in a mass ratio of 1:1-1:4 to obtain Ka-band low-loss self-biased composite ferrite powder;

[0014] Step 2: First ball milling

[0015] The composite ferrite powder obtained in step 1 is ball milled by a ball mill for 6 to 12 hours;

[0016] Step 3: Primary sintering

[0017] The ball mill obtained in step 2 is dried and sieved, and the temperature is first raised to 500-600 °C and kept at this temperature for 1-3 h; then the temperature is quickly raised to 900-1000 °C and kept at this temperature for 1-3 h; and the temperature is quickly raised to 1200-1300 °C again and kept at this temperature for 1-3 h;

[0018] Step 4: Doping

[0019] In the mixed sintered powder obtained in step 3, dopants are added according to the mass percentage of the Ka-band low-loss self-biased composite ferrite powder: 0.1-0.5 wt.% CuO and 0.1-0.5 wt.% SiO2;

[0020] Step 5: Secondary ball milling

[0021] The mixture obtained in step 4 was ball-milled in a ball mill for 12-18 h, and the particle size of the powder was controlled between 0.7-0.9 μm;

[0022] Step 6: Magnetic field forming

[0023] The ball mill obtained in step 5 is pressed and molded in a magnetic field molding machine, the molding magnetic field is 0.7-1.2 T, and the molding pressure is 90-150 MPa;

[0024] Step 7: Secondary sintering

[0025] The green body obtained in step 6 is subjected to secondary sintering at a sintering temperature of 1200-1300°C for a holding time of 4-10 hours. After sintering, it is naturally cooled to room temperature and taken out to obtain the Ka-band low-loss self-biased composite ferrite material.

[0026] Furthermore, in step 3, the temperature is increased to 900-1000°C at a heating rate of 15°C / min and kept at this temperature for 1-3 h.

[0027] Furthermore, in step 3, the temperature is increased to 1200-1300°C at a heating rate of 15°C / min and kept at this temperature for 1-3 h.

[0028] The performance of the Ka-band low-loss self-biased composite ferrite material obtained in step 7 is tested: saturation magnetization intensity 4π M s , residual magnetization 4π M r , coercivity H c Measured using the American LakeShore 8604 vibrating sample magnetometer; ferromagnetic resonance line width Δ H and dielectric loss tan d ε The anisotropic field is measured using the CK-XW-100 high-frequency integrated measurement system. H a The final technical indicators of the Ka-band low-loss self-biased composite ferrite material prepared by the present invention are as follows:

[0029] Saturation magnetization 4π M s ≥4200 Gs;

[0030] Remanence ratio M r / M s ≥0.90;

[0031] Coercivity H c ≥3580 Oe;

[0032] Anisotropy Field H a ≥13 kOe;

[0033] Ferromagnetic resonance line width Δ H ≤300 Oe;

[0034] Dielectric loss tan d ε ≤2×10 -3 .

[0035] Compared with the prior art, the present invention has the following beneficial effects:

[0036] The present invention mixes and sinters two microwave ferrite raw materials, NiZn and BaM ferrite, in one pot, and adopts a multi-step sintering technology to regulate the reaction generation of spinel intermediate products, NiZn and BaM ferrite, enhance the exchange coupling effect between the magnetic moments of NiZn and BaM ferrite, and improve the performance of composite ferrite materials. M r / M s and H c ; At the same time, through one-pot sintering, the NiZn and BaM grains are more evenly distributed and staggered, resulting in a higher density of the coupling material, corresponding to Δ H and tan d ε Smaller. The Ka-band low-loss self-biased composite ferrite material has both high 4π M s , M r / M s , H a , H c and low Δ H tan d ε Characteristics, suitable for the design and application of Ka-band micro-integrated circulator. DETAILED DESCRIPTION

[0037] The present invention is described in detail below in conjunction with specific examples and comparative examples. This example is implemented based on the technical solution of the present invention, and provides a detailed implementation method and specific operation process, but the present invention is not limited to the following examples.

[0038] A method for preparing a Ka-band low-loss self-biased composite ferrite material comprises the following steps:

[0039] Step 1: Ingredients

[0040] Weigh the NiZn ferrite raw material according to the ratio of "45.5 mol% NiO, 3.5 mol% CuO, 3.5 mol% ZnO, 47.5 mol% Fe2O3"; weigh the BaM ferrite raw material according to the ratio of "14.5 mol% BaO, 6.5 mol% ZnO, 3.5 mol% La2O3, 5.5 mol% CuO, 70mol% Fe2O3"; mix the NiZn and BaM ferrite raw materials, the mixing ratio is shown in the table below, and obtain Ka-band low-loss self-biased composite ferrite powder;

[0041]

[0042] Step 2: First ball milling

[0043] The composite ferrite powder obtained in step 1 is ball milled by a ball mill for 8 h;

[0044] Step 3: Primary sintering

[0045] The ball mill obtained in step 2 is dried and sieved, and the temperature is first raised to 600°C and kept at this temperature for 2 h; then the temperature is quickly raised to 950°C and kept at this temperature for 2 h; and the temperature is quickly raised to 1250°C again and kept at this temperature for 2 h;

[0046] Step 4: Doping

[0047] In the mixed sintered powder obtained in step 3, dopants are added according to the mass percentage of the Ka-band low-loss self-biased composite ferrite powder: 0.3 wt.% CuO and 0.2 wt.% SiO2;

[0048] Step 5: Secondary ball milling

[0049] The mixture obtained in step 4 was ball-milled in a ball mill for 16 h, and the particle size of the powder was controlled between 0.7 and 0.9 μm;

[0050] Step 6: Magnetic field forming

[0051] The ball mill obtained in step 5 is pressed and molded in a magnetic field molding machine, the molding magnetic field is 0.9 T, and the molding pressure is 120 MPa;

[0052] Step 7: Secondary sintering

[0053] The green body obtained in step 6 is subjected to secondary sintering at a sintering temperature of 1250° C. and a holding time of 8 h. After sintering, it is naturally cooled to room temperature and taken out to obtain the Ka-band low-loss self-biased composite ferrite material.

[0054] The performance of the Ka-band low-loss self-biased composite ferrite material obtained in step 7 is tested: saturation magnetization intensity 4π M s , residual magnetization 4π M r , coercivity H c Measured using the American LakeShore 8604 vibrating sample magnetometer; ferromagnetic resonance line width Δ H and dielectric loss tan d ε The anisotropic field is measured using the CK-XW-100 high-frequency integrated measurement system. H a It is derived from Kittel's formula.

[0055] In comparative example 1, the temperature was raised to 1250°C during the first sintering process in step 3 and kept at this temperature for 2 hours; and the dopant and the BaM ferrite raw material were added simultaneously during the doping process in step 4. In comparative example 2, the temperature was raised to 1250°C during the first sintering process in step 3 and kept at this temperature for 2 hours; and the dopant and the NiZn ferrite raw material were added simultaneously during the doping process in step 4.

[0056] The performance parameters of the Ka-band low-loss self-biased composite ferrite materials prepared based on the above formulation and process, Examples 1-4 and Comparative Examples 1-2 are as follows:

[0057]

[0058] The above contents are further detailed descriptions of the present invention in combination with specific preferred embodiments, and it cannot be determined that the specific implementation of the present invention is limited to these descriptions. For those skilled in the art of the present invention, several equivalent substitutions or obvious variations can be made without departing from the concept of the present invention, and the performance or use is the same, which should be regarded as belonging to the protection scope of the present invention.

Claims

1. A Ka-band low-loss self-biased composite ferrite material, characterized in that: including a main phase and a dopant; The main phase includes NiZn ferrite material and BaM ferrite material, wherein the NiZn ferrite material includes 40-60 mol% NiO, 1-5 mol% CuO, 1-5 mol% ZnO, and 40-50 mol% Fe2O3, and the BaM ferrite material includes 10-20 mol% BaO, 1-10 mol% ZnO, 1-5 mol% La2O3, 1-10 mol% CuO, and 60-75 mol% Fe2O3; the mass ratio of the NiZn ferrite material to the BaM ferrite material is 1:1-1:4; The weight percentage of dopants in the main phase, calculated as oxides: 0.1~0.5 wt.% CuO and 0.1~0.5 wt.% SiO2; The Ka-band low-loss self-biased composite ferrite material is prepared by the following steps: Step 1: Ingredients Weigh the NiZn ferrite raw material according to the ratio of "40-60 mol%NiO, 1-5 mol%CuO, 1-5 mol%ZnO, 40-50 mol%Fe2O3"; weigh the BaM ferrite raw material according to the ratio of "10-20 mol%BaO, 1-10 mol%ZnO, 1-5 mol%La2O3, 1-10 mol%CuO, 60-75mol%Fe2O3"; The NiZn and BaM ferrite raw materials are mixed in a mass ratio of 1:1 to 1:4 to obtain Ka-band low-loss self-biased composite ferrite powder; Step 2: First ball milling The composite ferrite powder obtained in step 1 is ball-milled for 6 to 12 h; Step 3: Primary sintering The ball mill obtained in step 2 is dried and sieved, and the temperature is first raised to 500-600 °C and kept at this temperature for 1-3 h; then the temperature is raised to 900-1000 °C and kept at this temperature for 1-3 h; and the temperature is raised again to 1200-1300 °C and kept at this temperature for 1-3 h; Step 4: Doping In the mixed sintered powder obtained in step 3, dopants are added according to the mass percentage of the Ka-band low-loss self-biased composite ferrite powder: 0.1-0.5 wt.% CuO and 0.1-0.5 wt.% SiO2; Step 5: Secondary ball milling The mixture obtained in step 4 was ball-milled for 12-18 h, and the particle size of the powder was controlled between 0.7-0.9 μm; Step 6: Magnetic field forming The ball mill obtained in step 5 is pressed into a mold, the molding magnetic field is 0.7-1.2 T, and the molding pressure is 90-150 MPa; Step 7: Secondary sintering The green body obtained in step 6 is subjected to secondary sintering at a sintering temperature of 1200-1300°C for a holding time of 4-10 h. After sintering, it is naturally cooled to room temperature and taken out to obtain a Ka-band low-loss self-biased composite ferrite material.

2. A method for preparing a Ka-band low-loss self-biased composite ferrite material, characterized in that: The following steps are involved: Step 1: Ingredients Weigh the NiZn ferrite raw material according to the ratio of "40-60 mol%NiO, 1-5 mol%CuO, 1-5 mol%ZnO, 40-50 mol%Fe2O3"; weigh the BaM ferrite raw material according to the ratio of "10-20 mol%BaO, 1-10 mol%ZnO, 1-5 mol%La2O3, 1-10 mol%CuO, 60-75mol%Fe2O3"; The NiZn and BaM ferrite raw materials are mixed in a mass ratio of 1:1 to 1:4 to obtain Ka-band low-loss self-biased composite ferrite powder; Step 2: First ball milling The composite ferrite powder obtained in step 1 is ball-milled for 6 to 12 h; Step 3: Primary sintering The ball mill obtained in step 2 is dried and sieved, and the temperature is first raised to 500-600 °C and kept at this temperature for 1-3 h; then the temperature is raised to 900-1000 °C and kept at this temperature for 1-3 h; and the temperature is raised again to 1200-1300 °C and kept at this temperature for 1-3 h; Step 4: Doping In the mixed sintered powder obtained in step 3, dopants are added according to the mass percentage of the Ka-band low-loss self-biased composite ferrite powder: 0.1-0.5 wt.% CuO and 0.1-0.5 wt.% SiO2; Step 5: Secondary ball milling The mixture obtained in step 4 was ball-milled for 12-18 h, and the particle size of the powder was controlled between 0.7-0.9 μm; Step 6: Magnetic field forming The ball mill obtained in step 5 is pressed into a mold, the molding magnetic field is 0.7-1.2 T, and the molding pressure is 90-150 MPa; Step 7: Secondary sintering The green body obtained in step 6 is subjected to secondary sintering at a sintering temperature of 1200-1300°C for a holding time of 4-10 h. After sintering, it is naturally cooled to room temperature and taken out to obtain the Ka-band low-loss self-biased composite ferrite material.

3. The method for preparing the Ka-band low-loss self-biased composite ferrite material according to claim 2, characterized in that: In step 3, the temperature is raised to 900-1000 °C at a heating rate of 15 °C / min and kept at this temperature for 1-3 h.

4. The method for preparing the Ka-band low-loss self-biased composite ferrite material according to claim 2, characterized in that: In step 3, the temperature is raised to 1200-1300 °C at a heating rate of 15 °C / min and kept at this temperature for 1-3 h.

Citation Information

Patent Citations

  • High specific saturation magnetization and high coercitive force strontium ferrite magnetic powder and preparation thereof

    CN101372417A

  • High-performance ferrite magnetic material and preparation method thereof

    CN108640669A